PENGALAMAN MENJADI SEORANG JURU KUNCI SUMBER MATA AIR KERAMAT DI KABUPATEN BOYOLALI: SEBUAH INTERPRETATIVE PHENOMENOLOGICAL ANALYSIS - Lia Sulistyani; Salma Salma (Faculty of Psychology, Diponegoro University, 2020)
Being a Jurukunci of a spring is not an easy job. It takes a sincere and professional attitude towards his work. Many people consider the job of a Jurukunci with one eye because it is not an easy job with low wages. Moreover the job of a Jurukunci is quite heavy because it costs a lot of time and energy. So far, there is still little research on the experience of being the Jurukunci of a sacred spring. The purpose of this study is to understand the experience of being a Jurukunci of a sacred spring. The approach used in this research is phenomenological qualitative research with Interpretative Phenomenological Analysis (IPA) data analysis techniques. There are selection three participants who are a jurukunci of sacred spring in boyolali in this study.Purposive sampling selection of participants with the following criteria: (1) the Jurukunci of a sacred spring in Boyolali, (2) had the experience of being a Jurukunci of a sacred spring in Boyolali for a minimum of five years, (3) willing to be the subject of research. The results showed that are three main themes, namely: (1) life principles, which include: work motivation, ways of thinking, sincerity in living life, (2) meaningfulness of work, which includes: attitudes towards work, positive impact of choosing work, and( 3) self-image, which includes: self-confidence, pride in being a caretaker, social relations with others.